Perfil genotípico de resistência do vírus Influenza A (H1N1) pandêmico aos inibidores da neuraminidase em pacientes procedentes da mesorregião de Belém no período de maio de 2009 a maio de 2012 - BARBAGELATA, Luana Soares (Universidade Federal do Pará, 2015)
Influenza virus is responsible for the flu, a disease that causes millions of hospitalizations and deaths every year. In severe infections, especially in people at risk with comorbidities for complications, antiviral become the main means for clinical management, mainly the neuraminidase inhibitors (INAs). By fact, in the 2009 pandemic episode the World Health Organization (WHO) recommends the use of Oseltamivir for the treatment of patients. However, due to viral genetic evolution emerged strains with mutations in the gene coding for the neuraminidase (NA) responsible for amino acid substitutions that lead to drug resistance INAs. Thus, WHO began recommending surveillance genotypic resistance to influenza viruses. Our study aimed to verify the occurrence of mutations in the NA encoding gene of Influenza virus A (H1N1) pandemic strains that could be related to INAs resistance in the Belém mesoregion from May 2009 to May 2012 and analyze, through modeling of proteins, NA amino acid substitutions that may be altering the protein conformation. During the study period, were received 2619 clinical samples at the Virus Respiratory Lab in Evandro Chagas Institute in Belém – Brazil, from patients presenting signs and symptoms of acute respiratory infection with up to five days from the start of symptoms. For the detection of the viral genome viral RNA extraction was made followed by real time RT- PCR using specific markers for Influenza A H1N1pdm, resulting in 744 (28.4%) positive samples. A portion of the positive samples were then inoculated in MDCK cells and isolated samples were then submitted to a new viral RNA extraction followed by real time RT-PCR and semi-nested reaction (PCR) using primers specific for the NA gene. Subsequent analysis was done in 3130xl ABI Prism automatic sequencer (Applied Biosystems ). Molecular modeling was performed to the NA gene using SWISS-MODEL software, MODELLER 9.10, Procheck, VERIFY3D and PYMOL. The analysis of partial sequences of neuraminidase showed no circulation of the H1N1 pdm with H275Y mutation, the principal involved in resistance to oseltamivir. However in two samples were identified the D199N substitution that has been reported in several studies showing a possible association with increased resistance to oseltamivir. The samples of 2012 showed two substitutions (V241I and N369K) which are relate to a possible role in offsetting the negative effects caused by the H275Y mutation. Molecular modeling shows that the mutation D199N caused a change in protein structure near the NA-antiviral binding site. Phylogenetic analysis revealed that 2012 samples formed an isolated cluster, showing a much more temporal variation than geographic. This represents the first study of drug resistance of influenza virus in H1N1pdm metropolitan mesoregion of Belém - Brazil an important tool for health professionals to adopt more effective strategies for disease management and the development of new anti-influenza drugs.